Priscian's De laude Anastasii imperatoris - Coyne, Patricia (My University, 1988)
Imperil panegyrics have often been dismissed as mere flattery of no literary merit and limited historical value. In recent years, increasing interest in the study if the history of the later Roman empire has led scholars and to take a fresh look at panegyrics and to examine their role in the society of the late antique world. Detailed studies of individual works are necessary for this examination and reevaluation of imperial panegyric. This thesis, consisting of translation and commentary, provides such a study, the first in English, of the Delaude Anastasii impreratoris, a verse panegyric of the emperor Anastasius (491-518) written in Constantinople by the sixth century author Priscian, best known for his work on Latin grammar.
Set in its literary context, the panegyric illustrates one stage in the Christianization of a secular literary genre. To praise his Christian emperor and justify his rule in terms of Christian political theory, the poet abandons the epic style and mythological allusions used by his predecessors in Latin verse panegyric. Instead, Priscian versifies the outline for imperial panegyric provided in rhetorical handbooks. Literary traditions, however, dictates that his language and poetic adornment be neutral, acceptable to both pagan and Christian, and as a result there are few overtly Christian elements in the poem.
In the panegyric; Priscian creates the image of an emperor chosen by God and protected by His might. The skillful development of and emphasis on such an image suggest that historically the poem should be dates to the later part of Anastasius' reign when religious controversy and armed rebellion threatened his throne. More specifically the panegyrist's portrait of the emperor, combined with reference to historical events, indicates that the poem may date to the year 513, the first year of the rebellion of Vitalian. Set in this context, the poem was probably aimed at dissident elements within Anastasius' court and administration.
Keywords: Roman Studies; Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures